2002
DOI: 10.1016/s0375-9601(02)00185-8
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic extrema in electronic susceptibility and heat capacity of mesoscopic systems

Abstract: Oscillating behaviour of the susceptibility χ and heat capacity C is considered for normal and superconducting mesoscopic systems (nanoclusters and quantum dots). It is proved that at low temperature an increasing magnetic field applied to a mesoscopic system generates local extrema of χ and C. A maximum for χ and a minimum for C simultaneously arise in those points of the field where crossings of quantum levels of the normal and superconducting mesoscopic systems take place.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…1). Numerous peaks in χ and C result from crossings of the Fermi level and an upper level nearest to it that gives at low temperatures a maximum in χ and simultaneously a minimum in C [13] as shown in the insert in Fig. 1.…”
Section: Results Of Calculationsmentioning
confidence: 96%
“…1). Numerous peaks in χ and C result from crossings of the Fermi level and an upper level nearest to it that gives at low temperatures a maximum in χ and simultaneously a minimum in C [13] as shown in the insert in Fig. 1.…”
Section: Results Of Calculationsmentioning
confidence: 96%
“…This result is found in qualitative agreement with those obtained in the calculations of the canonical gap of in Refs. [20,32] various T . For T /T c 0.2, the pairing gap undergoes a backbending, which will be discussed under Sec.…”
Section: B Results Within the Doubly-folded Multilevel Equidistant Mmentioning
confidence: 99%
“…(2), the rotational part ν = i exp(βγ M ν,i ) of the partition function Z(β, γ ) is calculated following Ref. [32]. The resulting canonical average value M(β, γ ) C = βZ(β, γ ) −1 ∂Z(β, γ )/∂γ of angular momentum, therefore, varies with T .…”
Section: Discussionmentioning
confidence: 99%
“…In Ref. [26] we showed that similar oscillations in C (and in the magnetic susceptibility) are stimulated by the increasing magnetic field H i.e. in that case the role of α was performed by H.…”
Section: Shape Resonances In the Fermion Heat Capacitymentioning
confidence: 80%